PERAN FASILITAS PENDIDIKAN DALAM MENINGKATKAN HASIL BELAJAR BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Cindy Arsita; Opi Andriani; Mulia Ningsih; Risa Fitri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
A brief description of educational facilities in improving learning outcomes for children with special needs at primary school 149/II Tanah Bekali. Educational facilities greatly affect the learning outcomes of students, especially for children with special needs (Abk). With adequate facilities and being an intermediary or learning media, it makes it easier for teachers to deliver learning materials to achieve learning goals. For children with special needs to understand the material being taught, they should use adequate facilities, so that the material conveyed by the teacher can be received properly like other students. This of course will greatly affect the learning outcomes of abk students (children with special needs) in learning. The more complete the facilities in the school, the more it will improve the quality of students and improve student learning outcomes. For this reason, adequate facilities are needed to improve the learning outcomes of abk (children with special needs).